Reconstruction of Human Resource Management in the Era of Disruption in the Study of Islamic Education - Hanapia, Cepi; Purwanto, Purwanto; Rahmatulloh, Aang; Muliasutisna, Asep; Indriani, Lisna (Journal of English Language and Education, 2025)
The disruption era requires an inclusive and comprehensive observation and research, especially in the world of education in Indonesia. God created humans as caliphs (God's representatives) on earth. Therefore, God gives something that can be seen by humans, heard by humans, felt by humans, and made by humans with the concept of thinking according to the teachings of Alquran. The Word of God, I sent Alqur'an down to the earth for people who want to think (have sense/faith). The famous French philosopher, Descartes said, "I think then I am". For God, nothing is impossible in this world. In the book al-Ghunyah, al-Jailani mentions that those who are pious in a hadith the Prophet said, "The definition of takwa is summarized in the words of Allah," Verily Allah commands (you) to be fair and do good, give to relatives, and Allah prohibit from vile actions, munkar, and hostility. He gives teaching to you so you can take lessons. " (Q.S. An-Nahl/16: 90). The lesson here is interpreted as a learning process in Islamic religious education in the reconstruction of human resource management. In Law No.20/2003 concerning National Education System, the implementation of education must hold several principles, namely education is held in a democratic and just manner and not discriminatory by upholding human rights, religious values, cultural values, and national plurality with a systemic unity with the system open and multi-meaningful. In addition, the implementation must also be in a process of civilization and empowerment of students that lasts a lifetime by giving example, developing willingness, and developing students' creativity in the learning process through developing a culture of reading, writing and counting for all citizens to empower all components of society through participation in the implementation and quality control of education services. The author uses descriptive research methods with library research research. The author makes use of the literature on education and human resource management. In the field of education the main purpose of research and development is not to formulate or test a theory, but to develop effective products for use in schools.